Short-Course or Total Neoadjuvant Chemotherapy in Resectable and Borderline Resectable Pancreatic Cancer - Current Status and Future Perspectives - Labori, Knut Jørgen (Frontiers in Surgery, 2022)
Neoadjuvant therapy improves overall survival compared with a surgery-first approach in patients with borderline resectable pancreatic cancer (BRPC). More high-quality evidence is required to determine whether neoadjuvant therapy has potential benefits and improves survival for patients with resectable pancreatic cancer (RPC). Most randomized controlled trials (RCTs) have explored short course neoadjuvant chemotherapy (SNT), but total neoadjuvant chemotherapy (TNT) is now the experimental arm of ongoing RCTs. This article reviews the current status of SNT and TNT in RPC and BRPC, and provides perspectives of future challenges and research directions in this field.